Pengembangan dan Implementasi Lembar Kerja Project Terhadap Keterampilan Pemanfaatan Lingkungan Siswa Kelas IX - Samputri, Salma; Arif, Rifda Mardian; Muhiddin, Nurhayani H (INSTITUT AGAMA ISLAM NEGERI AMBON, 2022)
This research is a research on developing student project sheets based on science environment technology and creativity (scientificity) to improve skills in using the environment both inside and outside school. This type of research is the Dick and Carey Research and Development (R&D) model with a quantitative and qualitative approach. Data collection techniques in this study used survey methods, observations and observation sheets for environmental utilization skills. The population of this study were all students in several schools in Makassar city and Gowa district, namely Al-Biruni Mandiri Quarantine Middle School, IT Al-Azhar 24 Makassar Islamic Middle School, National Middle School, Kalam Kudus Christian Middle School, and Sungguminasa 4 Middle School. The sampling technique uses the Random Sampling technique in determining the experimental and control classes. This data analysis technique uses descriptive statistics. This research resulted in: (1) New products regarding student project sheets based on Science Environment Technology and Creativity (Scientechvity), (2) Strategies and learning models for using the environment, and (3) Improving students' environmental utilization skills both inside and outside of school. Keywords: Project Sheet, SET, Creativity, Environment